Volume microscopy in biology: FIB-SEM tomography. (April 2019) - Kizilyaprak, Caroline; Stierhof, York-Dieter; Humbel, Bruno M.
Highlights: 3D imaging at high spatial resolution with electron microscopes. Summary of the current state of the art of volume microscopy. Serial sectioning, serial-block face scanning microscopy and focussed ion beam scanning microscopy. Focus on sample preparation for volume microscopy. Abstract: Volume microscopy has become an important method in cellular biology. In contrast to tedious serial sectioning volumes can now far more conveniently be obtained with serial-block face and focussed ion beam scanning electron microscopy. Serial-block face scanning electron microscopy is the instrument of choice for large volumes whereas focussed ion beam scanning electron microscopy has its merits in high voxel resolution. These aspects are discussed along with some specific applications of a focussed ion beam scanning electron microscope.